Folk Psychology and the Interpretation of Decision Theory - Johanna Thoma (Ergo, An Open Access Journal of Philosophy)
Most philosophical decision theorists and philosophers of the social sciences believe that decision theory is and should be in the business of providing folk psychological explanations of choice behaviour, and that it can only do so if we understand the preferences, utilities and probabilities that feature in decision-theoretic models as ascriptions of mental states not reducible to choice. The behavioural interpretation of preference and related concepts, still common in economics, is consequently cast as misguided. This paper argues that even those who strive to provide folk psychological explanations should side with the economists, and adopt a behavioural interpretation of the preferences featuring in decision-theoretic models. Under a mentalistic interpretation of preference, decision-theoretic models do not straightforwardly provide ordinary folk psychological explanations. Instead, they involve controversial enough commitments about the mental causes of choice to not only fail to adequately capture much unreflective decision-making, but also many intentional, reason-based and instrumentally rational choices. Satisfactory folk psychological explanation in fact only comes indirectly from inferring more fundamental conative attitudes from a pattern of decision-theoretic preferences. And the behavioural interpretation does a better job at facilitating such inferences. My argument extends to the related concepts of utility and probability.